Buenas prácticas para la producción tradicional de semilla de papa de calidad - Fundación Proinpa (2016)
In Bolivia, the cultivation of potatoes is strategic for food sovereignty and one of the main sources of income for most of the peasant families in the highlands. Most of the rural agricultural communities engaged in potato cultivation continue to use traditional or informal sources of potato seed. It is estimated that more than 95% of potato seeds comes from the informal system, which is capable of producing a broad variety of seeds at accessible prices. Local technologies and knowledge to maintain good quality seeds exist, but they are not implemented by all producers. This training manual provides tools and knowledge to improve the quality of the seeds produced, and to rescue and innovate good practices for the production of quality seed in the context of the traditional seed systems in the highlands.